Modeling and optimization of IPMC actuator for autonomous jellyfish vehicle (AJV) - Akle, Barbar J. (2017)
Ionomeric Polymer Metal Composite (IPMC) actuators generate high flexural strains at small voltage amplitudes of 2-5V. IPMCs bend toward the anode when a potential drop is applied across its thickness. The actuation mechanism is due to the motion of ions inside it; which requires a form of hydration to dissociate and mobilize the charges. In our group IPMCs are developed either water based or Ionic Liquid based which is also known as the dry IPMCs. This combination of small voltage requirement with operation in both dry and underwater conditions makes the IPMCs a viable alternative for an Autonomous Jellyfish Vehicle (AJV). In this study, we estimate the mechanical properties of IPMC actuator having curved geometry using FEM model to match the experimental deformation. We combine the results from an electric model to estimate charge accumulated on electrode surface with piezoelectric model to estimate stress due to this charge accumulation. In the last step, the results are integrated with a structural model to simulate the actuator deformation. We have designed an AJV with embedded IPMC actuators using these properties to achieve the curvature of relaxed and contracted Jellyfish (Aurelia Aurita). Bio-mimetic deformation profile was achieved by using structural mechanics of beams with large deformation with only application of +/- 0.8V to optimized beam within 8.1% error norm in relaxed state and 21.3% in contracted state, with only -0.24% to 0.26% maximum flexural strain at maximum curvature point in contracted state.